Pertumbuhan Misellium Bibit F1 Jamur Tiram Dan JamurMerang Pada Media Kardus Dan Media Biji Jagung - Sugiyanto, Apryza Ryzchy Pratama Putra Negara, Dra.Suparti, M.Si (2016)
Misellium is a collection of fungal hyphae that sustains life on other organisms that have died, so need another organism to supply needed nutrients such as cellulose, lignin, and nutrients. Corn kernels can be used as a medium for the growth of mycelium fungus because it contains a lot of nutrients to grow. Cardboard is produced from wood that can be used as a growth medium misellium compounds that contain cellulose. This study aims to determine the growth misellium F1 seed oyster mushroom and mushroom which grow on the media box and media corn kernels. The method used in this study was an experimental method completely randomized design (CRD) factorial design consisting of two factors. The first factor was the type of media used in the form of media and media cardboard corn grain bran mixture and the second factor was the type of fungus that is used in the form of a tiram mushrooms and mushroom. Analysis of data used qualitative descriptive with the calculation of standard deviation. The results showed the fastest growth occured in media misellium cardboard with misellium 8.5 cm long and the longest growth occured in media misellium corn kernels with a length of 1.1 cm.